Hybridization and the species problem in conservation. Issue 1 (1st February 2015) - Fitzpatrick, Benjamin M.; Ryan, Maureen E.; Johnson, Jarrett R.; Corush, Joel; Carter, Evin T.
Abstract: Most biologists recognize the "species phenomenon" as a real pattern in nature: Biodiversity is characterized by discontinuities between recognizable groups classified as species. Many conservation laws focus on preventing species extinction. However, species are not fixed. Discontinuities evolve gradually and sometimes disappear. Exactly how to define particular species is not always obvious. Hybridization between taxonomic species reminds us that species classification is not a perfect representation of nature. Classification is a model that is very useful, but not adequate in all cases. Conservationists often confront questions about how to apply species-based laws when hybridization confounds classification. Development of sophisticated techniques and nuanced interpretation of data in the basic study of species and speciation has exposed the need for deeper education in genetics and evolution for applied conservationists and decision makers. Here we offer a brief perspective on hybridization and the species problem in conservation. Our intended audience is conservation practitioners and decision-makers more than geneticists and evolutionary biologists. We wish to emphasize that the goals and premises of legislative classification are not identical to those of scientific classification. Sometimes legal classification is required when the best available science indicates that discrete classification is not an adequate model for the case. Establishing legal status and level of protection for hybrids and hybrid populations means choosing from a range of scientifically valid alternatives. Although we should not abandon species-based approaches to conservation, we must recognize their limitations and work to clarify the roles of science and values in ethical and legal decisions.